Epidural analgesia combined with transversus abdominis plane block with liposomal bupivacaine reduces pain after caesarean delivery: a double-blind, randomised controlled trial - Ma, Wei; Long, Yanxi; Ye, Shanshan; Tao, Qiang; Wang, Yang; Xu, Tao (Frontiers in Medicine, 2025)
BackgroundSustained release of bupivacaine can be achieved by encapsulating bupivacaine within multivesicular liposomes, providing localised analgesia for up to 72 h. This study aimed to evaluate whether a multimodal analgesic approach integrating epidural analgesia with liposomal bupivacaine enhanced transversus abdominis plane block could extend the interval to initial opioid use and thus reduce the total post-operative opioid requirements in women undergoing caesarean section.MethodsWomen scheduled for elective caesarean delivery under combined spinal-epidural anaesthesia were randomly assigned to a liposomal bupivacaine or placebo group. All participants were given 0.75% ropivacaine 15 mg intrathecally at L3–L4 interspace. Before surgical closure, 0.6 mg of epidural hydromorphone was administered. Bilateral ultrasound-guided lateral transversus abdominis plane blocks were performed after surgery. The liposomal bupivacaine group received 133 mg liposomal bupivacaine in 20 mL fluid per side, whereas the placebo control group received 20 mL saline per side. Postoperative analgesia included scheduled oral acetaminophen and self-administered boluses of oxycodone as needed. The primary outcomes were 24- and 48-h oxycodone consumption.ResultsA total of 128 women were enrolled. The median [interquartile range (IQR)] postoperative cumulative oxycodone consumption was significantly lower in the liposomal bupivacaine group than in the placebo group at 24 h [2 (0–5) mg vs. 4 (1–8) mg, p = 0.009] and 48 h [8 (0–13) mg vs. 10 (4–18) mg, p = 0.022], and the median (IQR) interval to first patient-controlled analgesia use was significantly longer in the liposomal bupivacaine group than in the placebo group [22 (12–48) vs. 8 (4–18) h; p < 0.001].ConclusionEpidural hydromorphone combined with liposomal bupivacaine enhances transversus abdominis plane block, prolongs analgesia duration and reduces opioid requirements in the first 48 h after caesarean-section.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=237618, Identifier [ChiCTR2400087477].